Memory and Identity in the Emotive Map of Alain Resnais’ Hiroshima Mon Amour (1959) - Jytte Holmqvist (NANO, 2014)
The focus of this article is Alain Resnais’ representation of collective and individual memory and identity in Hiroshima Mon Amour (1959). The film is based on Marguerite Duras’ script from 1958 and remains faithful to this original text. With partial reference to Giuliana Bruno’s views on imaginary cities and urban cartography, the screened urban space will here be read as an emotive map in which the individual love story between the protagonists unfolds against the backdrop of their almost equally intimate relationship with the historically abused city of Hiroshima. This, in Bruno’s words helps create an affective “map of love” (243) or a “body-city on a tender map” (242). The paper highlights the fluid relationship between the protagonists and their environment, as well as the semi-documentary aspects of a film that establishes an effective dialogue between past and present.